2016
DOI: 10.1002/2015wr017894
|View full text |Cite
|
Sign up to set email alerts
|

Identification of contaminant source architectures—A statistical inversion that emulates multiphase physics in a computationally practicable manner

Abstract: The goal of this work is to improve the inference of nonaqueous-phase contaminated source zone architectures (CSA) from field data. We follow the idea that a physically motivated model for CSA formation helps in this inference by providing relevant relationships between observables and the unknown CSA. Typical multiphase models are computationally too expensive to be applied for inverse modeling; thus, state-of-the-art CSA identification techniques do not yet use physically based CSA formation models. To overc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 66 publications
1
27
0
Order By: Relevance
“…In the first category, Gorelick et al (1983) identified the groundwater pollution source information through an optimization model using linear programming and multiple regression; Wagner (1992) employed a non-liner maximum likelihood method to estimate source location and flux; Mahar and Datta (2000) used a nonlinear optimization model for estimating the magnitude, location and duration of groundwater pollution sources with binding equality constraints; Yeh et al (2007) developed a hybrid approach, which combines simulated annealing, tabu search and a three-dimensional groundwater flow and solute transport model to solve the source identification problem; and Ayvaz (2010) utilized a harmony search-based simulation-optimization model to determine the source location and release histories by using an implicit solution procedure. In the second category, Bagtzoglou et al (1992) applied a particle method to estimate, probabilistically, source location and spill-time history; Woodbury and Ulrych (1996) used a minimum relative entropy approach to recover the release and evolution histories of a groundwater contaminant plume in a onedimensional system; Neupauer and Wilson (1999) employed a backward location model based on adjoint state method (BPM-ASM) to identify a contaminant source; Butera et al (2013) utilized a simultaneous release function and source location identification (SRSI) method to identify the release history and source location of an injection in a groundwater aquifer; and Koch and Nowak (2016) derived and applied a Bayesian reverse-inverse methodology to infer source zone architectures and aquifer parameters.…”
Section: Introductionmentioning
confidence: 99%
“…In the first category, Gorelick et al (1983) identified the groundwater pollution source information through an optimization model using linear programming and multiple regression; Wagner (1992) employed a non-liner maximum likelihood method to estimate source location and flux; Mahar and Datta (2000) used a nonlinear optimization model for estimating the magnitude, location and duration of groundwater pollution sources with binding equality constraints; Yeh et al (2007) developed a hybrid approach, which combines simulated annealing, tabu search and a three-dimensional groundwater flow and solute transport model to solve the source identification problem; and Ayvaz (2010) utilized a harmony search-based simulation-optimization model to determine the source location and release histories by using an implicit solution procedure. In the second category, Bagtzoglou et al (1992) applied a particle method to estimate, probabilistically, source location and spill-time history; Woodbury and Ulrych (1996) used a minimum relative entropy approach to recover the release and evolution histories of a groundwater contaminant plume in a onedimensional system; Neupauer and Wilson (1999) employed a backward location model based on adjoint state method (BPM-ASM) to identify a contaminant source; Butera et al (2013) utilized a simultaneous release function and source location identification (SRSI) method to identify the release history and source location of an injection in a groundwater aquifer; and Koch and Nowak (2016) derived and applied a Bayesian reverse-inverse methodology to infer source zone architectures and aquifer parameters.…”
Section: Introductionmentioning
confidence: 99%
“…These computations employed 100 CPU cores, in parallel, each with 128 GB of memory. It is anticipated that a stochastic approach, based on forward flow and transport models and similar to that presented in Koch and Nowak (2016), would require more than 10 5 transport model runs prior to application of rejection sampling for conditioning the source zone 10.1029/2019WR026481…”
Section: Discussionmentioning
confidence: 99%
“…Further research should also consider the uncertainty related to hydrogeological property characterization and flow and transport boundary conditions. Some steps have already been made in that direction (Koch and Nowak, 2016), but were limited to common multi-Gaussian conductivity fields. In addition, a regular grid discretization might compromise the ability to accurately locate the contaminant source in the presence of a strong flow path.…”
Section: Discussionmentioning
confidence: 99%